Incidence of post operative surgical site infection in thyroid surgery following single dose of prophylactic antibiotic (Bangladesh Journal of Otorhinolaryngology, 2020)
Surgical site infection after thyroid surgery is a less common incidence. Prophylactic antibiotic before surgery and empirical antibiotic therapy after surgery is a common practice in our country. But international guidelines do not suggest antibiotic in clean surgical procedure.Aim: To compare the incidence of surgical site infection after thyroid surgery with and without empirical antibiotic therapy.Method: It was a cross sectional study, done from July 2010 to December 2010 in 3 medical college hospitals in Dhaka city. Total 100 cases were included in this study, 50 cases for study in which only single prophylactic antibiotic used half an hour before operation, 50 cases for control in which 7 days antibiotic used per orally in addition to prophylaxis.Result: Among 100 cases male were 24 & female 76 (M: F= 1:3.2). Oldest patient was 56 yrs & youngest 21yrs. 47% patient operated for solitary thyroid nodule, 35% multinodular goiter & only 6% diffuse goiter. 47% patient was done hemithyroidectomy & only 7% total thyroidectomy. All the operations were completed within 2 hours where 40% within one hour. No surgical site infections were found in both study and control cases.Conclusion: There is no statistical difference between routine antibiotic use and no use of antibiotic after thyroid surgery.Bangladesh J Otorhinolaryngol; April 2016; 22(1): 15-20